Pemberian Terapi Latihan dan Edukasi dalam Upaya Meningkatkan Kemampuan Aktivitas Fungsional pada Lansia dengan Osteoarthritis Knee di Puskesmas Rampal Celaket - Simon Panyonga; Syarif Hidayatullah; Qonita Nabila; Dinda Permata Putri; Ika Niswatul Chamidah (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2024)
Osteoarthritis is a joint disorder that develops degeneratively due to chronic inflammation in the joint. Symptoms involve the gradual breakdown of cartilage, osteophyte formation, and changes in the synovial membrane. Osteoarthritis sufferers often experience a decrease in daily activities. In particular, Knee Osteoarthritis is the most common type of Osteoarthritis that causes joint pain and limitation of motion in the knee, characterized by damage to the joint cartilage and Diarthrodial structures. In order for people to prevent Osteoarthritis Knee, it is important to identify the risk factors that can lead to the condition. With this understanding, it is hoped that people can avoid the risk factors as part of prevention efforts. By distributing leaflets and conducting Knee Osteoarthritis examinations and daily activity evaluations on patients, the results showed an increase in functional activity in the elderly after undergoing routine exercise therapy. In conclusion, through this counseling activity, increasing public awareness, especially among the elderly, about the importance of preventing Osteoarthritis Knee. Continuous preventive and curative efforts are needed to reduce the incidence rate of Osteoarthritis Knee in the community.